2022
DOI: 10.1101/2022.05.17.492338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Negative Periocular Pressure on Biomechanics of the Optic Nerve Head and Cornea: A Computational Modeling Study

Abstract: PurposeTo evaluate the effects of negative periocular pressure (NPP), and concomitant intraocular pressure (IOP) lowering, on the biomechanics of the optic nerve head (ONH) and cornea.MethodsWe developed a validated finite element (FE) model of the eye to compute tissue biomechanical strains induced in response to NPP delivered using the Multi-Pressure Dial (MPD) system. The model was informed by clinical measurements of IOP lowering and was based on published tissue properties. We also conducted sensitivity a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…Application of the negative pressure goggles has been proposed as a novel non-medical and non-invasive treatment for glaucoma and recent computational modeling has predicted that IOP will reduce with the application of negative pressure goggles initially due to scleral expansion and longer term with increasing episcleral outflow. 16 Another recent computational study reported a reduction in IOP with exposure to negative pressure 24 , which is consistent with the expected mechanical response of a generic closed vessel under pressure expose to reduce external pressure. Results of numerical models based on simplified and generic ocular morphology and mechanical properties would of course omit all the eye-specific and orbital characteristics that may mediate the response of IOP to varying extra orbital pressure, as observed by our study.…”
Section: Discussionsupporting
confidence: 70%
“…Application of the negative pressure goggles has been proposed as a novel non-medical and non-invasive treatment for glaucoma and recent computational modeling has predicted that IOP will reduce with the application of negative pressure goggles initially due to scleral expansion and longer term with increasing episcleral outflow. 16 Another recent computational study reported a reduction in IOP with exposure to negative pressure 24 , which is consistent with the expected mechanical response of a generic closed vessel under pressure expose to reduce external pressure. Results of numerical models based on simplified and generic ocular morphology and mechanical properties would of course omit all the eye-specific and orbital characteristics that may mediate the response of IOP to varying extra orbital pressure, as observed by our study.…”
Section: Discussionsupporting
confidence: 70%
“…We used the average first principal Lagrangian strain (Ξ I ) and SCLA estimates for the most compliant case from each age model and ensured that the error relative to an exhaustively refined mesh was less than 1% for Ξ I and SCLA (relative to the baseline SCLA of the corresponding age model). The meshes were generated using the Frontal algorithm, and ten steps of smoothing and optimization were conducted to enhance mesh quality [30].…”
Section: Model Geometry Creation and Fe Mesh Generationmentioning
confidence: 99%
“…Specifically, we decreased the elemental characteristic edge length in the TM by a factor of 4 and in the PL region by a factor of 8. The meshes were generated using the Frontal algorithm, and ten steps of smoothing and optimization were conducted to enhance mesh quality (Safa et al, 2022b).…”
Section: Model Geometry Creation and Fe Mesh Generationmentioning
confidence: 99%